Effective execution of the flight in quadruple jumps in figure skating - Knoll, Ka.; Seidel, I. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
For a high final score figure skaters need quadruple jumps (QJ) with perfect execution. QJ are very difficult and have a high risk of falling. Therefore the purpose of this study was to identify reserves in the flight phase for a safe execution of jumps with more than three rotations. The complete number of turns in the flight phases is necessary to perform a safe landing. Perfect quadruple jumps in different competitions with international participation of 12 world class athletes have been selected for the study and analysed with a 3D kinematic analysis. The primary aim of the study has been to identify reserves for a perfect execution on the basis of moment of inertia. In addition the study aimed at characterizing the movement when preparing the landing movement with only a very short time available for the skater, especially in jumps with more than three turns.